Negative electrode composition, negative electrode for lithium secondary battery comprising the same, lithium secondary battery comprising the negative electrode, and method of preparing the negative electrode composition
Patent Information
- Application Number
- CN202280044193.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-11-11
- Filing Date
- 2022-11-03
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2042-11-03
AI Technical Summary
该SEI能够通过抑制负极与电解液之间反应所需的电子转移来防止电解质的分解反应,从而稳定化负极的结构,而由于充电反应是不可逆反应,因此会造成锂离子的消耗,因此人们一直在研究更稳定并且能够发挥上述优点的SEI层
[0024]根据本申请的负极组合物的特征在于,其包含高含量的纯Si粒子,因此能够获得具有高容量和高密度的负极,同时为了解决例如因包含高含量纯Si粒子而引起的体积膨胀的问题,利用包含氟的碳层涂覆包含高含量纯Si粒子的硅系活性材料本身并使用,从而能够解决体积膨胀问题,并且发挥硅系活性材料的优势。
Smart Images

Figure CN117546314B_ABST
Abstract
Description
Technical Field
[0001] This application claims priority and benefit to Korean Patent Application No. 10-2021-0154386, filed with the Korean Intellectual Property Office on November 11, 2021, the entire contents of which are incorporated herein by reference.
[0002] This application relates to a negative electrode composition, a negative electrode for a lithium secondary battery comprising the negative electrode, a lithium secondary battery comprising the negative electrode, and a method for preparing the negative electrode composition. Background Technology
[0003] As the use of fossil fuels increases rapidly, the demand for alternative or clean energy sources is also growing. As part of this trend, the most active research area is the use of electrochemical reactions for power generation and energy storage.
[0004] Currently, representative examples of electrochemical devices using such electrochemical energy include secondary batteries, and their applications are expanding.
[0005] With the technological development and increasing demands of mobile devices, the demand for secondary batteries as an energy source is rapidly increasing. Among such secondary batteries, lithium-ion batteries, characterized by high energy density and voltage, long cycle life, and low self-discharge rate, have been commercialized and are widely used. Furthermore, as electrodes for such high-capacity lithium-ion batteries, researchers have been actively exploring methods for preparing high-density electrodes with even higher energy density per unit volume.
[0006] Generally, a secondary battery consists of a positive electrode, a negative electrode, an electrolyte, and a separator. The negative electrode contains a negative electrode active material for inserting and de-intercalating lithium ions from the positive electrode, and silicon-based particles with high discharge capacity can be used as the negative electrode active material.
[0007] In particular, recently, to meet the demand for high-density energy batteries, researchers are actively exploring methods to improve capacity by using silicon-based compounds such as Si / C or SiOx as the negative electrode active material. These silicon-based compounds have a capacity up to 10 times higher than graphite-based materials. While silicon-based compounds are high-capacity materials, exhibiting significantly greater capacity compared to currently used graphite, they suffer from a problem: rapid volume expansion during charging disrupts conductive paths, thereby degrading battery performance.
[0008] Therefore, in order to solve the problems when the silicon-based compounds are used as negative electrode active materials, measures to adjust the driving potential and measures to suppress volume expansion itself have been discussed, such as methods to further coat a thin film on the active material layer and methods to adjust the particle size of the silicon-based compounds, and various measures to prevent the conductive path from being broken. However, the application of these measures has limitations, because the performance of the battery may be degraded instead. Therefore, the commercialization of batteries with negative electrodes containing high silicon-based compounds is still limited.
[0009] Furthermore, the positive electrode of a lithium-ion battery is typically made using lithium-intercalating compounds such as LiCoO2 and LiMn2O4, while the negative electrode is made using non-lithium-intercalating materials such as carbon-based and Si-based materials. During charging, lithium ions intercalated in the positive electrode move to the negative electrode through the electrolyte, and during discharging, lithium ions move from the negative electrode to the positive electrode. The lithium moving from the positive to the negative electrode during the charging reaction reacts with the electrolyte to form a solid electrolyte interface (SEI) on the surface of the negative electrode, which is a passivation film. This SEI can prevent electrolyte decomposition by suppressing the electron transfer required for the reaction between the negative electrode and the electrolyte, thereby stabilizing the structure of the negative electrode. However, since the charging reaction is irreversible, it leads to the consumption of lithium ions. Therefore, researchers have been studying more stable SEI layers that can exert the aforementioned advantages.
[0010] Therefore, it is necessary to study a silicon-based active material that can prevent the conductive path from being damaged by the volume expansion of the silicon-based compound, even when the silicon-based compound is used as the active material to improve capacity performance, and it is also necessary to study the formation of a more stable SEI layer.
[0011] <Related Technical Documents>
[0012] Japanese Patent Application Publication No. 2009-080971 Summary of the Invention
[0013] [Technical Issues]
[0014] It has been found that, recognizing the above-mentioned problems, when a coated silicon-based active material is used to improve the volume expansion problem of the silicon-based active material, and the coating is specifically doped with specific elements, the rapid volume expansion of the silicon-based active material during charge and discharge is mitigated, while a more stable film is formed on the negative electrode.
[0015] Therefore, this application relates to a negative electrode composition, a negative electrode for a lithium secondary battery comprising the negative electrode, a lithium secondary battery comprising the negative electrode, and a method for preparing the negative electrode composition.
[0016] [Technical Solution]
[0017] One exemplary embodiment of the present specification provides a negative electrode composition, comprising: a silicon-based active material; a negative electrode conductive material; and a negative electrode binder, wherein a surface of the silicon-based active material comprises a carbon coating, the carbon coating is doped with fluorine (F), the silicon-based active material comprises one or more selected from the group consisting of SiOₓ (x=0) and SiOₓ (0<x<2), and based on 100 parts by weight of the silicon-based active material, the content of the SiOₓ (x=0) is 70 parts by weight or more.
[0018] In one exemplary embodiment, a method for preparing a negative electrode composition is provided, the method comprising: preparing a silicon-based active material, the silicon-based active material comprising a carbon coating doped with fluorine (F) on a surface thereof; forming a mixture by mixing a negative electrode conductive material and a negative electrode binder; performing first mixing by adding water to the mixture; and performing second mixing by adding the silicon-based active material comprising the carbon coating doped with fluorine (F) to the mixed mixture, wherein the silicon-based active material comprises one or more selected from the group consisting of SiOₓ (x=0) and SiOₓ (0<x<2), and based on 100 parts by weight of the silicon-based active material, the content of the SiOₓ (x=0) is 70 parts by weight or more.
[0019] In another exemplary embodiment, a negative electrode for a lithium secondary battery is provided, comprising: a negative electrode current collector layer; and a negative electrode active material layer formed on one surface or two surfaces of the negative electrode current collector layer, wherein the negative electrode active material layer comprises the negative electrode composition according to the present application.
[0020] Finally, a lithium secondary battery is provided, comprising: a positive electrode; the negative electrode for a lithium secondary battery according to the present application; a separator disposed between the positive electrode and the negative electrode; and an electrolyte.
[0021] [Advantageous Effects]
[0022] The negative electrode composition according to an exemplary embodiment of the present invention is a negative electrode composition in which, when a silicon-based active material (which is a high-capacity material) is used to manufacture a high-capacity battery, properties of the silicon-based active material itself are adjusted instead of adjusting properties of a conductive material and a binder according to the volume expansion of the silicon-based active material, and is characterized in that the surface of the silicon-based active material comprises a carbon coating, and by using a carbon coating doped with fluorine (F) as the carbon coating, rapid volume expansion of the silicon-based active material during charging and discharging is alleviated, while the fluorine doped into the carbon coating can react with FEC, so that a more stable LiF film is formed on the negative electrode on the basis of forming an SEI layer.
[0023] Although graphite-based compounds are generally used alone as negative electrode active materials in the related art, as the demand for high-capacity batteries has increased recently, attempts to use silicon-based compounds in combination to increase capacity are also on the rise. In particular, the negative electrode composition according to an exemplary embodiment of the present invention is such a negative electrode composition, in which the silicon-based active material contains one or more selected from the group consisting of SiOₓ(x=0) and SiOₓ(0<x<2), and based on 100 parts by weight of the silicon-based active material, the content of the SiOₓ(x=0) is 70 parts by weight or more. Since it contains a high content of pure Si particles, it is characterized in that a negative electrode with high capacity and high density can be produced.
[0024] The negative electrode composition according to the present application is characterized by containing a high content of pure Si particles, so that a negative electrode with high capacity and high density can be obtained. Meanwhile, in order to solve the problem of volume expansion caused by, for example, containing a high content of pure Si particles, the silicon-based active material itself containing a high content of pure Si particles is coated with a fluorine-containing carbon layer for use, thereby solving the volume expansion problem and exerting the advantages of the silicon-based active material.
[0025] That is, compared with the case of using the existing silicon-based active material, the case of using the surface-treated silicon-based active material containing a specific content of silicon particles as in the present invention is characterized in that the volume expansion during charge and discharge can also be minimized by using the negative electrode composition according to the present invention. Brief Description of the Drawings
[0026] Figure 1 is a diagram showing the stacked structure of a negative electrode for a lithium secondary battery according to an exemplary embodiment of the present application.
[0027] Figure 2 is a diagram showing the stacked structure of a lithium secondary battery according to an exemplary embodiment of the present application.
[0028] <Reference Numeral Description>
[0029] 10: Negative electrode current collector layer
[0030] 20: Negative electrode active material layer
[0031] 30: Separator
[0032] 40: Positive electrode active material layer
[0033] 50: Positive electrode current collector layer
[0034] 100: Negative electrode for lithium secondary battery
[0035] 200: Positive electrode for lithium secondary battery Detailed Description of Embodiments
[0036] Before describing the present invention, some terms will be defined first.
[0037] In this specification, when a part "contains" a constituent element, unless otherwise specified, this does not mean that other constituent elements are excluded, but rather that other constituent elements may be further contained.
[0038] In this specification, 'p to q' refers to the range of 'above p and below q'.
[0039] In this specification, "specific surface area" is measured by the BET method, specifically using a BELSORP-Mino II manufactured by BEL Japan Co., Ltd., calculated from the amount of nitrogen adsorbed at liquid nitrogen temperature (77K). That is, in this application, the BET specific surface area can refer to the specific surface area measured by the aforementioned method.
[0040] In this specification, "Dn" refers to the average particle size, specifically the particle size at the n% point of the cumulative particle number distribution based on particle size. That is, D50 is the particle size at the 50% point of the cumulative particle number distribution based on particle size, D90 is the particle size at the 90% point of the cumulative particle number distribution based on particle size, and D10 is the particle size at the 10% point of the cumulative particle number distribution based on particle size. Alternatively, the average particle size can be measured using laser diffraction. Specifically, after dispersing the powder to be tested in a dispersion medium, the resulting dispersion is introduced into a commercially available laser diffraction particle size measurement device (e.g., Microtrac S3500). The particle size distribution is calculated by measuring the difference in diffraction patterns corresponding to the particle size as the particles pass through the laser beam.
[0041] In this specification, the fact that a polymer contains monomers as monomeric units means that the monomers participate in the polymerization reaction and are thus included in the polymer as repeating units. In this specification, when a polymer contains monomers, it is interpreted in the same way as when the polymer contains monomers as monomeric units.
[0042] In this specification, the term 'polymer' is understood to be used in the broad sense, including copolymers, unless otherwise specified as 'homogeneous polymer'.
[0043] In this specification, weight-average molecular weight (Mw) and number-average molecular weight (Mn) are molecular weights derived from polystyrene measured by gel permeation chromatography (GPC) using commercially available monodisperse polystyrene polymers (standard samples) with various degrees of polymerization as standard materials. Unless otherwise stated, molecular weight in this specification refers to weight-average molecular weight.
[0044] Hereinafter, the present invention will be described in detail with reference to the accompanying drawings, so that those of ordinary skill in the art to which the present invention pertains can easily implement the present invention. However, the present invention may be embodied in various different forms and is not limited to the following description.
[0045] One exemplary embodiment of the present specification provides a negative electrode composition, comprising: a silicon-based active material; a negative electrode conductive material; and a negative electrode binder, wherein a surface of the silicon-based active material comprises a carbon coating, the carbon coating is doped with fluorine (F), the silicon-based active material comprises one or more selected from the group consisting of SiOₓ (x=0) and SiOₓ (0<x<2), and based on 100 parts by weight of the silicon-based active material, the content of the SiOₓ (x=0) is 70 parts by weight or more.
[0046] The negative electrode composition according to an exemplary embodiment of the present invention is a negative electrode composition in which, when a silicon-based active material (which is a high-capacity material) is used to manufacture a high-capacity battery, properties of the silicon-based active material itself are adjusted instead of adjusting properties of the conductive material and the binder in response to volume expansion of the silicon-based active material, and is characterized in that the surface of the silicon-based active material comprises a carbon coating, and by using a fluorine (F)-doped carbon coating as the carbon coating, rapid volume expansion of the silicon-based active material during charging and discharging is alleviated, while the fluorine doped into the carbon coating can react with FEC, so that a more stable LiF film is formed on the negative electrode on the basis of forming an SEI layer.
[0047] In one exemplary embodiment of the present application, there is provided a negative electrode composition, wherein the silicon-based active material comprises one or more selected from the group consisting of SiOₓ (x=0) and SiOₓ (0<x<2), and based on 100 parts by weight of the silicon-based active material, the content of the SiOₓ (x=0) is 70 parts by weight or more.
[0048] In another exemplary embodiment, based on 100 parts by weight of the silicon-based active material, the content of the SiOₓ (x=0) may be 70 parts by weight or more, preferably 80 parts by weight or more, more preferably 90 parts by weight or more, and the content thereof may be 100 parts by weight or less, preferably 99 parts by weight or less, more preferably 95 parts by weight or less.
[0049] In one exemplary embodiment of the present application, the silicon-based active material may comprise metal impurities, in which case the metal impurities are metals that may normally be comprised in the silicon-based active material, and based on 100 parts by weight of the entire silicon-based active material, the content thereof may be 1 part by weight or less, or 0.1 parts by weight or less.
[0050] In an exemplary embodiment of the present application, for the silicon-based active material, in particular, pure silicon (Si) may be used as the silicon-based active material. Using pure silicon (Si) as the silicon-based active material may refer to that, based on 100 parts by weight of the silicon-based active material in total as described above, pure Si particles (SiOₓ(x=0)) that are not combined with other particles or elements are contained in the above range.
[0051] In the silicon-based active material according to the present application, based on 100 parts by weight of the silicon-based active material, the content of the SiOₓ(x=0) is 70 parts by weight or more. Compared with a silicon-based active material using a SiOₓ(0<x<2)-based material as a main material, the SiOₓ(0<x<2)-based material has a disadvantage that the theoretical capacity is far lower than that of the silicon-based active material of the present application. That is, when a SiOₓ(0<x<2)-based active material is used, no matter what treatment is performed on the active material itself, it is impossible to achieve conditions with equivalent charge and discharge capacity as the case having the silicon-based active material of the present invention.
[0052] Since the silicon-based active material has a significantly higher capacity than graphite-based active materials used in the related art, attempts to apply the silicon-based active material are increasing, but such attempts are only limited to cases where a small amount of the silicon-based active material is mixed with the graphite-based active material for use and the like, because the silicon-based active material has a high volume expansion rate during charge and discharge processes.
[0053] Therefore, in the case of the present invention, while using only a pure silicon-based active material as the negative electrode active material to improve capacity performance, a specific material is coated on the surface of the silicon-based active material as described above to solve the above problems. The present invention is characterized in that, while the volume expansion of the silicon-based active material is alleviated particularly by the carbon coating, the fluorine doped into the carbon coating reacts with FEC, so that a more stable LiF inorganic film is formed on the basis of forming the SEI layer, thereby solving the existing problems.
[0054] On the other hand, the silicon-based active material of the present invention can have an average particle size (D50) of 5 μm to 10 μm, specifically 5.5 μm to 8 μm, and more specifically 6 μm to 7 μm. When the average particle size is within the above range, the viscosity of the negative electrode slurry is formed within a suitable range because the specific surface area of the particles is within a suitable range. Therefore, the dispersion of the particles constituting the negative electrode slurry is promoted. Furthermore, when the size of the silicon-based active material is equal to or greater than the lower limit range mentioned above, the composite material composed of conductive material and binder in the negative electrode slurry provides an excellent contact area between the silicon particles and the conductive material, thereby increasing the possibility of a continuous conductive network and improving the capacity retention rate. On the other hand, when the average particle size meets the above range, excessively large silicon particles are eliminated, thereby forming a smooth negative electrode surface, thus preventing uneven current density during charging and discharging.
[0055] In one exemplary embodiment of this application, the silicon-based active material typically has a characteristic BET specific surface area. The BET specific surface area of the silicon-based active material is preferably from 0.01 to 150.0 m². 2 / g, more preferably 0.1 to 100.0m 2 / g, particularly preferably 0.2 to 80.0m 2 / g, with the most preferred value being 0.2 to 18.0m 2 / g. The BET specific surface area was measured using DIN 66131 (using nitrogen).
[0056] In one exemplary embodiment of this application, the silicon-based active material may exist, for example, in a crystalline or amorphous form, and is preferably not porous. The silicon particles are preferably spherical or fragmented. Alternatively, but less preferably, the silicon particles may also have a fibrous structure, or exist in the form of a silicon-containing film or coating.
[0057] In one exemplary embodiment of this application, a negative electrode composition is provided, wherein, based on 100 parts by weight of the negative electrode composition, the silicon-based active material is present in an amount of 60 parts by weight or more.
[0058] In another exemplary embodiment, based on 100 parts by weight of the negative electrode composition, the content of the silicon-based active material can be 60 parts by weight or more, preferably 65 parts by weight or more, more preferably 70 parts by weight or more, and its content can be 95 parts by weight or less, preferably 90 parts by weight or less, more preferably 80 parts by weight or less.
[0059] The negative electrode composition according to the present application has the following characteristics: even when a silicon-based active material with a significantly high capacity is used within the above range, by using a specific surface coating capable of suppressing the volume expansion rate during charge and discharge processes, the performance of the negative electrode does not deteriorate even when contained in the above range, and the output characteristics during charge and discharge are excellent.
[0060] In an exemplary embodiment of the present application, the silicon-based active material may have a non-spherical form, and its sphericity is, for example, 0.9 or less, for example 0.7 to 0.9, for example 0.8 to 0.9, for example 0.85 to 0.9.
[0061] In the present application, the sphericity is determined by the following Formula 1, where A is the area and P is the boundary line.
[0062] [Formula 1]
[0063] 4πA / P 2
[0064] The surface of the silicon-based active material according to the present application comprises a carbon coating, the carbon coating is doped with fluorine (F), and the silicon-based active material itself is formed of a material including SiOₓ(x=0) and SiOₓ(0<x<2), and includes the following two cases: each of one or more particles selected from the group consisting of SiOₓ(x=0) and SiOₓ(0<x<2) contained in the silicon-based active material has a fluorine-containing carbon coating; and secondary particles formed by aggregation of one or more particles selected from the group consisting of SiOₓ(x=0) and SiOₓ(0<x<2) have a fluorine-containing carbon coating.
[0065] In an exemplary embodiment of the present application, the silicon-based active material may include one or more selected from the group consisting of SiOₓ(x=0), SiOₓ(0<x<2), SiC and Si alloys.
[0066] In an exemplary embodiment of the present application, there is provided a negative electrode composition, wherein the fluorine (F) doped in the carbon coating is formed by a single bond between carbon and fluorine (F).
[0067] In an exemplary embodiment of the present application, the thickness of the carbon coating may satisfy a range of 1 nm or more and 20 nm or less, preferably 5 nm or more and 15 nm or less, and 10 nm or more and 15 nm or less.
[0068] In an exemplary embodiment of the present application, based on 100 parts by weight of the silicon-based active material, the carbon content contained in the carbon coating may be 5 parts by weight or more and 20 parts by weight or less.
[0069] In another exemplary embodiment, based on 100 parts by weight of silicon-based active material, the carbon content contained in the carbon coating can be in the range of 5 parts by weight or more and 20 parts by weight or less, preferably 7 parts by weight or more and 15 parts by weight or less.
[0070] In one exemplary embodiment of this application, a negative electrode composition is provided, based on 100 parts by weight of silicon-based active material, having a fluorine (F) content of 0.1 parts by weight or more and 20 parts by weight or less.
[0071] In another exemplary embodiment, based on 100 parts by weight of silicon-based active material, the fluorine (F) can be 0.1 parts by weight or more and 20 parts by weight or less, preferably 0.1 parts by weight or more and 10 parts by weight or less, more preferably 0.2 parts by weight or more and 5 parts by weight or less, and can satisfy the range of 3 parts by weight or less and 1 part by weight or less.
[0072] Since the fluorine is contained based on the silicon-based active material, the coating thickness is appropriate, thereby maintaining the capacity per unit weight. It is characterized in that, while mitigating the rapid volume expansion of the silicon-based active material during charge and discharge, the carbon coating can be doped with fluorine in the above-mentioned weight parts to react with FEC, thereby forming a more stable LiF film on the negative electrode in addition to forming an SEI layer.
[0073] In related technologies, graphite-based compounds are typically used as negative electrode active materials. However, recently, with the increasing demand for high-capacity batteries, there has been an increase in attempts to use silicon-based compounds in combination to improve capacity. However, even though the properties of the silicon-based active material itself have been adjusted as described above according to this application, in some cases, its volume still expands rapidly during charging and discharging, which may lead to damage to the conductive paths formed in the negative electrode active material layer.
[0074] Therefore, in one exemplary embodiment of this application, the negative electrode conductive material may comprise one or more of the group consisting of point conductive materials, planar conductive materials and linear conductive materials.
[0075] In one exemplary embodiment of this application, the dot-like conductive material can be used to enhance the conductivity of the negative electrode, and is preferably a conductive material that is conductive without causing chemical changes. Specifically, the conductive material may be at least one selected from the group consisting of natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal cracking black, conductive fibers, fluorocarbons, aluminum powder, nickel powder, zinc oxide, potassium titanate, titanium oxide, and polyphenylene derivatives, and may preferably contain carbon black for achieving high conductivity and excellent dispersibility.
[0076] In one exemplary embodiment of this application, the dot-shaped conductive material may have a density of 40m. 2 / g or more and 70m 2 / g or less, preferably 45m 2 / g or more and 65m 2 / g or less, more preferably 50m 2 / g or more and 60m 2 BET specific surface area below / g.
[0077] In one exemplary embodiment of this application, the functional group content (volatile substances) of the dot-shaped conductive material can be 0.01% or more and 1% or less, preferably 0.01% or more and 0.3% or less, and more preferably 0.01% or more and 0.1% or less.
[0078] Specifically, when the functional group content of the dot-shaped conductive material meets the above-mentioned range, functional groups are present on the surface of the dot-shaped conductive material, so that when water is used as a solvent, the dot-shaped conductive material can be smoothly dispersed in the solvent. In particular, in this invention, due to the use of silicon particles and a specific binder, the functional group content of the dot-shaped conductive material can be reduced, thus this invention has excellent effects in improving dispersibility.
[0079] In one exemplary embodiment of this application, the dot-shaped conductive material having a functional group content within the above-mentioned range is included together with the silicon-based active material, and the functional group content can be adjusted according to the degree of heat treatment of the dot-shaped conductive material.
[0080] In other words, when manufacturing the dot-shaped conductive material, a high functional group content may mean the presence of a large number of foreign objects, and a low functional group content may mean that more heat treatment processing has been performed. Furthermore, the dot-shaped conductive material according to this application is characterized in that, in order to meet the functional group content within the above-mentioned range, the dot-shaped conductive material is partially heat-treated to meet the functional group content range.
[0081] Specifically, because the dispersibility of the dot-shaped conductive material is improved, even if the content of the dot-shaped conductive material is increased in the negative electrode slurry with the same solid content, the viscosity of the negative electrode slurry can be maintained at a suitable level, thereby improving the uniformity of the formed negative electrode while maintaining a stable processability.
[0082] In one exemplary embodiment of this application, the dot-shaped conductive material may have a particle size of 10 nm to 100 nm, preferably 20 nm to 90 nm, and more preferably 20 nm to 60 nm.
[0083] In one exemplary embodiment of this application, the conductive material may comprise a planar conductive material.
[0084] The planar conductive material can increase the surface contact between silicon particles in the negative electrode to improve conductivity, while suppressing the breakage of the conductive path caused by volume expansion, and can be manifested as a plate-shaped conductive material or a bulk conductive material.
[0085] In one exemplary embodiment of this application, the planar conductive material may comprise at least one selected from the group consisting of plate graphite, graphene, graphene oxide, and graphite flakes, and may preferably be plate graphite.
[0086] In one exemplary embodiment of this application, the planar conductive material may have an average particle size (D50) of 2 μm to 7 μm, specifically 3 μm to 6 μm, and more specifically 4 μm to 5 μm. When the average particle size meets the above range, sufficient particle size is beneficial for dispersion without causing an excessive increase in the viscosity of the negative electrode slurry. Therefore, when dispersing particles using the same equipment and time, the dispersion effect is excellent.
[0087] In one exemplary embodiment of this application, a negative electrode composition is provided, wherein the planar conductive material has a D10 of 0.5 μm or more and 1.5 μm or less, a D50 of 2.5 μm or more and 3.5 μm or less, and a D90 of 7.0 μm or more and 15.0 μm or less.
[0088] In one exemplary embodiment of this application, a high specific surface area planar conductive material with a high BET specific surface area or a low specific surface area planar conductive material can be used as the planar conductive material.
[0089] In one exemplary embodiment of this application, a high specific surface area planar conductive material or a low specific surface area planar conductive material can be used as the planar conductive material without limitation. However, since the electrode performance may be affected to some extent by the dispersion effect, it may be particularly desirable to use a low specific surface area planar conductive material that will not cause dispersion problems as the planar conductive material according to this application.
[0090] In one exemplary embodiment of this application, the planar conductive material may have a 1m 2 BET specific surface area above / g.
[0091] In another exemplary embodiment, the planar conductive material may have a 1m 2 / g or more and 500m 2 / g or less, preferably 5m 2 / g or more and 300m2 / g or less, preferably 5m 2 / g or more and 300m 2 BET specific surface area below / g.
[0092] In another exemplary embodiment, the planar conductive material is a high specific surface area planar conductive material, and the BET specific surface area can meet 50m². 2 / g or more and 500m 2 / g or less, preferably 80m 2 / g or more and 300m 2 / g or less, more preferably 100m 2 / g or more and 300m 2 The range below / g.
[0093] In another exemplary embodiment, the planar conductive material is a low specific surface area planar conductive material, and the BET specific surface area can meet the requirement of 1m². 2 / g or more and 40m 2 / g or less, preferably 5m 2 / g or more and 30m 2 / g or less, preferably 5m 2 / g or more and 25m 2 The range below / g.
[0094] As other conductive materials, linear conductive materials such as carbon nanotubes can exist. These carbon nanotubes can be bundled carbon nanotubes. A bundled carbon nanotube can contain multiple carbon nanotube units. Specifically, unless otherwise stated, the term 'bundled' as used herein refers to a secondary shape in the form of a bundle or rope, wherein multiple carbon nanotube units are arranged side-by-side or wound in an orientation substantially the same as the longitudinal axis of the carbon nanotube units. In the carbon nanotube unit, the graphite sheet has a cylindrical shape with a diameter on the nanometer scale and has an sp2 bond structure. In this case, the carbon nanotube unit can exhibit conductive or semiconductor properties depending on the curl angle and structure of the graphite sheet. Compared to wound carbon nanotubes, bundled carbon nanotubes can be uniformly dispersed during anode fabrication and can smoothly form a conductive network in the anode, thereby improving the conductivity of the anode.
[0095] In one exemplary embodiment of this application, a negative electrode composition is provided, wherein, based on 100 parts by weight of the negative electrode composition, the content of the negative electrode conductive material is 10 parts by weight or more and 40 parts by weight or less.
[0096] In another exemplary embodiment, based on 100 parts by weight of the negative electrode composition, the content of the negative electrode conductive material may be 10 parts by weight or more and 40 parts by weight or less, preferably 10 parts by weight or more and 30 parts by weight or less, and more preferably 10 parts by weight or more and 25 parts by weight or less.
[0097] In one exemplary embodiment of this application, a negative electrode composition is provided, wherein the negative electrode conductive material comprises a planar conductive material and a linear conductive material, and based on 100 parts by weight of the negative electrode conductive material, the content of the planar conductive material is 80 parts by weight or more and 99.5 parts by weight or less, and the content of the linear conductive material is 0.5 parts by weight or more and 20 parts by weight or less.
[0098] In another exemplary embodiment, based on 100 parts by weight of negative electrode conductive material, the content of the planar conductive material can be 80 parts by weight or more and 99.5 parts by weight or less, preferably 85 parts by weight or more and 99 parts by weight or less, and more preferably 90 parts by weight or more and 98 parts by weight or less.
[0099] In another exemplary embodiment, based on 100 parts by weight of negative electrode conductive material, the content of the linear conductive material can be more than 0.5 parts by weight and less than 20 parts by weight, preferably more than 1 part by weight and less than 15 parts by weight, and more preferably more than 2 parts by weight and less than 10 parts by weight.
[0100] In one exemplary embodiment of this application, since the negative electrode conductive material comprises point-like conductive material, planar conductive material and linear conductive material and each satisfies the composition and ratio, the negative electrode conductive material has the following characteristics: the service life characteristics of existing lithium secondary batteries are not greatly affected, and in particular, when planar conductive material and linear conductive material are included, the number of chargeable and dischargeable sites of the battery is increased, thereby resulting in excellent output characteristics at high C-rate and reduced high-temperature gas generation.
[0101] The structure of the negative electrode conductive material according to this application is completely different from that of the conductive material applied to the positive electrode. That is, the negative electrode conductive material according to this application is used to obtain contact points between silicon-based active materials that have undergone significant electrode volume expansion due to charging and discharging, while the positive electrode conductive material acts as a buffer during rolling and also imparts partial conductivity. Its structure and function are completely different from those of the negative electrode conductive material of this invention.
[0102] Furthermore, the negative electrode conductive material according to this application is applied to silicon-based active materials, and its structure is completely different from that of the conductive material applied to graphite-based active materials. That is, the conductive material used in electrodes with graphite-based active materials has only small particles relative to the active material, and therefore has the characteristics of enhancing output characteristics and imparting partial conductivity. Its structure and function are completely different from the negative electrode conductive material used together with silicon-based active materials in this invention.
[0103] In one exemplary embodiment of this application, the plate-shaped conductive material used as the negative electrode conductive material has a structure and function different from that of carbon-based active materials typically used as negative electrode active materials. Specifically, the carbon-based active material used as the negative electrode active material can be artificial graphite or natural graphite, and refers to materials processed into spherical or dot-shaped forms for use in order to promote the storage and release of lithium ions.
[0104] In contrast, the plate-shaped conductive material used as the negative electrode conductive material is a material with a planar or plate-like shape, and can be plate-shaped graphite. That is, the plate-shaped conductive material is a material included to maintain the conductive path in the negative electrode active material layer, and refers to a material used to ensure the conductive path in a planar form in the negative electrode active material layer, rather than serving to store and release lithium.
[0105] In other words, the fact that plate-shaped graphite is used as a conductive material in this application means that the plate-shaped graphite is processed into a planar or plate-like shape and used as a material to ensure the conductive path rather than to store or release lithium. In this case, the included negative electrode active material has high capacity characteristics for lithium storage and release and serves to store and release all lithium ions transferred from the positive electrode.
[0106] In contrast, in this application, the use of carbon-based active materials as active materials refers to processing the carbon-based active materials into dots or spheres and using them as materials for storing or releasing lithium.
[0107] In one exemplary embodiment of this application, the negative electrode adhesive may comprise at least one material selected from the group consisting of polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidene fluoride, polyacrylonitrile, polymethyl methacrylate, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, polyacrylic acid, ethylene propylene diene monomer (EPDM), sulfonated EPDM, styrene-butadiene rubber (SBR), fluororubber, polyacrylic acid, and materials wherein hydrogen is substituted by Li, Na, Ca, etc., and may also comprise various copolymers thereof.
[0108] The negative electrode binder according to an exemplary embodiment of the present application functions to support the active material and the conductive material, thereby preventing distortion and structural deformation of the negative electrode structure during volume expansion and relaxation of the silicon-based active material, and all common binders can be applied as long as the above functions are satisfied. Specifically, water-based binders can be used, and more specifically, PAM-based binders can be used.
[0109] In an exemplary embodiment of the present application, based on 100 parts by weight of the negative electrode composition, the content of the negative electrode binder may be 30 parts by weight or less, preferably 25 parts by weight or less, more preferably 20 parts by weight or less, and the content thereof may be 5 parts by weight or more, or 10 parts by weight or more.
[0110] Compared with the existing carbon-based negative electrode, when a Si-based material is used in the negative electrode, the water-based binder is applied in the above parts by weight, so that a dot-shaped conductive material with a low functional group content can be used, and according to the above feature, the dot-shaped conductive material has hydrophobicity, which is characterized by excellent bonding strength between the conductive material and the binder.
[0111] In an exemplary embodiment of the present application, there is provided a method of preparing a negative electrode composition, the method comprising: preparing a silicon-based active material having a fluorine (F)-doped carbon coating on its surface; forming a mixture by mixing a negative electrode conductive material and a negative electrode binder; performing first mixing by adding water to the mixture; and performing second mixing by adding the silicon-based active material having a fluorine (F)-doped carbon coating to the mixed mixture, wherein the silicon-based active material contains one or more selected from the group consisting of SiOx (x=0) and SiOx (0<x<2), and the content of SiOx (x=0) is 70 parts by weight or more based on 100 parts by weight of the silicon-based active material.
[0112] In the method for preparing the negative electrode composition, each component contained in the negative electrode composition may be the same as described above.
[0113] In an exemplary embodiment of the present application, there is provided a method of preparing a negative electrode composition, wherein preparing the silicon-based active material having a fluorine (F)-doped carbon coating on its surface comprises: adding the silicon-based active material to a polymer solution containing fluorine (F); bonding the polymer containing fluorine (F) to the surface of the silicon-based active material by adding ethanol to the polymer solution; and carbonizing the bonded polymer.
[0114] In an exemplary embodiment of the present application, the carbonization of the bonded polymer may be carbonizing the polymer containing fluorine (F) on the surface of the silicon-based active material.
[0115] In one exemplary embodiment of this application, fluorine (F)-containing polymers can be used without limitation, as long as they are materials that provide fluorine (F) and carbon (C) atoms. Specifically, polyvinylidene fluoride (PVdF), Teflon, etc., can be used, but the fluorine (F)-containing polymers are not limited thereto.
[0116] In one exemplary embodiment of this application, a solvent for polymer solutions containing fluorine (F) can be used without limitation, as long as it is capable of dissolving the polymer containing fluorine (F). In particular, dimethylformamide (DMF) can be used.
[0117] In one exemplary embodiment of this application, adding the silicon-based active material to a polymer solution containing fluorine (F) may include adding the silicon-based active material according to this application to a polymer solution containing fluorine (F), and may also include stirring for a period of 1 to 12 hours after addition.
[0118] In one exemplary embodiment of this application, a fluorine-doped carbon coating can be formed on the surface of the silicon-based active material of this application by carbonization of the polymer.
[0119] In one exemplary embodiment of this application, the carbonization of the polymer may include heat treatment in an inert gas atmosphere in a high-temperature furnace at 500°C to 1000°C for 30 minutes to 3 hours.
[0120] Through the above carbonization process, the silicon-based active material according to this application can be surface modified into a silicon-based active material containing a carbon coating doped with fluorine (F) on its surface.
[0121] In one exemplary embodiment of this application, a method for preparing a negative electrode composition is provided, wherein in a first mixing step and a second mixing step, mixing is performed at a speed of 2,000 rpm to 3,000 rpm for 10 minutes to 60 minutes.
[0122] In one exemplary embodiment of this application, a negative electrode for a lithium secondary battery can be formed by coating a negative electrode slurry containing the negative electrode composition onto one or both surfaces of a current collector.
[0123] In one exemplary embodiment of this application, the negative electrode slurry may comprise: a negative electrode composition; and a slurry solvent.
[0124] In one exemplary embodiment of this application, the solid content of the negative electrode slurry can be between 5% and 40%.
[0125] In another exemplary embodiment, the solid content of the negative electrode slurry can be in the range of 5% or more and 40% or less, preferably 7% or more and 35% or less, and more preferably 10% or more and 30% or less.
[0126] The solid content of the negative electrode slurry can refer to the content of the negative electrode composition contained in the negative electrode slurry, and can refer to the content of the negative electrode composition based on 100 parts by weight of the negative electrode slurry.
[0127] When the solid content of the negative electrode slurry meets the above-mentioned range, the present invention has the following characteristics: since the viscosity is appropriate during the formation of the negative electrode active material layer, the negative electrode active material layer can be effectively formed by minimizing the particle aggregation phenomenon of the negative electrode composition.
[0128] In one exemplary embodiment of this application, a negative electrode for a lithium secondary battery is provided, comprising: a negative electrode current collector layer; and a negative electrode active material layer formed on one or both surfaces of the current collector layer, the negative electrode active material layer comprising a negative electrode composition according to this application.
[0129] Figure 1 This is a diagram illustrating the stacked structure of a negative electrode for a lithium secondary battery according to an exemplary embodiment of this application. Specifically, it can be confirmed that the negative electrode 100 for a lithium secondary battery includes a negative electrode active material layer 20 on one surface of the negative electrode current collector layer 10. Figure 1 A layer of negative electrode active material formed on one surface is shown, but the layer of negative electrode active material may be contained on both surfaces of the negative electrode current collector layer.
[0130] In one exemplary embodiment of this application, the negative electrode current collector typically has a thickness of 1 μm to 100 μm. The negative electrode current collector is not particularly limited, as long as it has high conductivity without causing chemical changes to the battery. For example, copper, stainless steel, aluminum, nickel, titanium, calcined carbon, copper or stainless steel surface-treated with carbon, nickel, titanium, silver, etc., aluminum-cadmium alloys, etc., can be used. Furthermore, the negative electrode current collector can increase the bonding strength of the negative electrode active material by forming fine irregularities on its surface, and the negative electrode current collector can be used in various forms, such as films, sheets, foils, meshes, porous bodies, foams, and nonwoven fabrics.
[0131] In one exemplary embodiment of this application, a negative electrode for a lithium secondary battery is provided, wherein the negative electrode current collector layer has a thickness of 1 μm or more and 100 μm or less, and the negative electrode active material layer has a thickness of 20 μm or more and 500 μm or less.
[0132] However, the thickness can be modified in various ways depending on the type and purpose of the negative electrode used, and is not limited thereto.
[0133] In one exemplary embodiment of this application, the porosity of the negative electrode active material layer can be in the range of 10% or more and 60% or less.
[0134] In another exemplary embodiment, the porosity of the negative electrode active material layer can be in the range of 10% or more and 60% or less, preferably 20% or more and 50% or less, and more preferably 30% or more and 45% or less.
[0135] The porosity varies depending on the composition and content of the silicon-based active material, conductive material, and binder contained in the negative electrode active material layer. In particular, since the silicon-based active material and conductive material according to this application are contained in a specific composition and content and satisfy the above range, the conductivity and resistance in the electrode are characterized by having a suitable range.
[0136] In one exemplary embodiment of this application, a lithium secondary battery is provided, comprising: a positive electrode; a negative electrode for a lithium secondary battery according to this application; a separator disposed between the positive electrode and the negative electrode; and an electrolyte.
[0137] Figure 2 This is a diagram illustrating the stacked structure of a lithium secondary battery according to an exemplary embodiment of this application. Specifically, it can be seen that the negative electrode 100 for the lithium secondary battery includes a negative electrode active material layer 20 on one surface of the negative electrode current collector layer 10, and the positive electrode 200 for the lithium secondary battery includes a positive electrode active material layer 40 on one surface of the positive electrode current collector layer 50. It is shown that the negative electrode 100 and the positive electrode 200 for the lithium secondary battery are formed as electrodes stacked with a separator 30 inserted therebetween.
[0138] A secondary battery according to an exemplary embodiment of this specification may specifically include the aforementioned negative electrode for a lithium secondary battery. Specifically, the secondary battery may include a negative electrode, a positive electrode, a separator inserted between the positive and negative electrodes, and an electrolyte, and the negative electrode is the same as described above. Since the negative electrode has been described in detail, its specific description will be omitted.
[0139] The positive electrode may include a positive electrode current collector and a positive electrode active material layer formed on the positive electrode current collector and containing positive electrode active material.
[0140] In the positive electrode, the positive electrode current collector is not particularly limited, as long as it is conductive and will not cause chemical changes to the battery. For example, stainless steel, aluminum, nickel, titanium, sintered carbon, or aluminum or stainless steel with a surface treatment of carbon, nickel, titanium, silver, etc., can be used. Furthermore, the positive electrode current collector can typically have a thickness of 3 μm to 500 μm, and the adhesion of the positive electrode active material can be enhanced by forming fine irregularities on the surface of the current collector. For example, the positive electrode current collector can be used in various forms, such as films, sheets, foils, meshes, porous bodies, foams, and nonwoven fabrics.
[0141] The positive electrode active material can be a commonly used positive electrode active material. Specifically, the positive electrode active material includes: layered compounds, such as lithium cobalt oxide (LiCoO2) and lithium nickel oxide (LiNiO2), or compounds replaced by one or more transition metals; lithium iron oxide, such as LiFe3O4; lithium manganese oxide, such as Li... 1+c1 Mn 2-c1 O4 (0≤c1≤0.33), LiMnO3, LiMn2O3 and LiMnO2; lithium copper oxide (Li2CuO2); vanadium oxides, such as LiV3O8, V2O5 and Cu2V2O7; Ni-site type lithium nickel oxide, represented by the chemical formula LiNi 1-c2 M c2 O2 (here, M is selected from at least one of the group consisting of Co, Mn, Al, Cu, Fe, Mg, B, and Ga, and c2 satisfies 0.01≤c2≤0.6); lithium manganese composite oxide, represented by the chemical formula LiMn 2-c3 M c3 O2 (here, M is selected from at least one of the group consisting of Co, Ni, Fe, Cr, Zn and Ta, and c3 satisfies 0.01≤c3≤0.6) or Li2Mn3MO8 (here, M is selected from at least one of the group consisting of Fe, Co, Ni, Cu and Zn); LiMn2O4 in which Li in the chemical formula is partially replaced by alkaline earth metal ions, etc., but not limited to these. The positive electrode can be Li metal.
[0142] In one exemplary embodiment of this application, the positive electrode active material comprises a lithium composite transition metal compound containing nickel (Ni), cobalt (Co) and manganese (Mn), the lithium composite transition metal compound comprising single particles or secondary particles, and the single particles may have an average particle size (D50) of more than 1 μm.
[0143] For example, the single particle may have an average particle size (D50) of 1 μm or more and 12 μm or less, 1 μm or more and 8 μm or less, 1 μm or more and 6 μm or less, greater than 1 μm or 12 μm or less, greater than 1 μm or 8 μm or less, or greater than 1 μm or 6 μm or less.
[0144] Even when the single particles are formed into small particles with an average particle size (D50) of 1 μm or more but less than 12 μm, the particle strength can still be excellent. For example, at a density of 650 kgf / cm², the particle strength can be exceptionally high. 2 Under pressure compression, the single particle can have a particle strength of 100 to 300 MPa. As a result, even at 650 kgf / cm², 2 The strong rolling of the single particles can also reduce the phenomenon of increased particle number in the electrode due to particle cracking, thereby improving the lifespan characteristics of the battery.
[0145] The single particle can be prepared by mixing a transition metal precursor and a lithium raw material and then calcining the resulting mixture. The secondary particle can be prepared by a different method than the single particle, and its composition can be the same as or different from that of the single particle.
[0146] There are no particular limitations on the method of forming the single particles, but in general, single particles can be formed by increasing the firing temperature to achieve overfiring, and the single particles can be prepared by using additives such as grain growth promoters that facilitate overfiring or by changing the starting materials.
[0147] For example, the sintering is carried out at a temperature capable of forming single particles. To form these single particles, the sintering needs to be performed at a higher temperature than when preparing secondary particles; for example, with the same precursor composition, the sintering needs to be performed at a temperature approximately 30°C to 100°C higher than when preparing secondary particles. The sintering temperature for forming the single particles can vary depending on the metal composition of the precursor. For example, when it is desired to form high-Ni NCM-based lithium composite transition metal oxides with a nickel (Ni) content of 80 mol% or more into single particles, the sintering temperature can be 700°C to 1000°C, preferably approximately 800°C to 950°C. When the sintering temperature meets the above range, a cathode active material containing single particles with excellent electrochemical properties can be prepared. When the sintering temperature is below 790°C, a cathode active material containing lithium composite transition metal compounds in the form of secondary particles can be prepared, while when the sintering temperature exceeds 950°C, over-sintering may occur, making it impossible to properly form a layered crystal structure, thereby reducing electrochemical properties.
[0148] In this specification, the term "single particle" is used to distinguish it from secondary particles, which are aggregates of tens to hundreds of primary particles in related art, and includes the concept of a single particle consisting of one primary particle and a quasi-single particle as an aggregate of 30 or fewer primary particles.
[0149] Specifically, in this invention, the single particle can be a single particle consisting of a primary particle, or a quasi-single particle as an aggregate of 30 or fewer primary particles, and the secondary particle can be an aggregate of several hundred primary particles.
[0150] In one exemplary embodiment of this application, the lithium composite transition metal compound used as the positive electrode active material further comprises secondary particles, and the average particle size (D50) of the single particles is smaller than the average particle size (D50) of the secondary particles.
[0151] In this invention, the single particle can be a single particle consisting of a primary particle, or a quasi-single particle as an aggregate of 30 or fewer primary particles, and the secondary particle can be an aggregate of several hundred primary particles.
[0152] The aforementioned lithium complex transition metal compounds may also contain secondary particles. Secondary particles refer to the form formed by the aggregation of primary particles, and can be distinguished from the concept of a single particle, which includes a single primary particle, a single particle, or a quasi-single particle as an aggregation of 30 or fewer primary particles.
[0153] The secondary particles may have a particle size (D50) of 1 μm to 20 μm, 2 μm to 17 μm, preferably 3 μm to 15 μm. The secondary particles may have a particle size of 0.05 μm. 2 / g to 10m 2 / g, preferably 0.1m 2 / g to 1m 2 / g, more preferably 0.3m 2 / g to 0.8m 2 Specific surface area (BET) per g.
[0154] In other exemplary embodiments of this application, the secondary particles are aggregates of primary particles, and the primary particles have an average particle size (D50) of 0.5 μm to 3 μm. Specifically, the secondary particles may be in the form of an aggregate of several hundred primary particles, and the primary particles may have an average particle size (D50) of 0.6 μm to 2.8 μm, 0.8 μm to 2.5 μm, or 0.8 μm to 1.5 μm.
[0155] When the average particle size (D50) of the primary particles meets the above-mentioned range, a single-particle positive electrode active material with excellent electrochemical properties can be formed. When the average particle size (D50) of the primary particles is too small, the number of primary particles that form lithium nickel oxide particles increases, thus reducing the inhibition of particle cracking during rolling; while when the average particle size (D50) of the primary particles is too large, the lithium diffusion path inside the primary particles becomes longer, thus increasing the resistance and potentially degrading the output characteristics.
[0156] According to other exemplary embodiments of this application, the average particle size (D50) of the single particle is characterized by being smaller than the average particle size (D50) of the secondary particles. Therefore, even if the single particle is formed with a small particle size, the single particle can still have excellent particle strength, and the excellent particle strength can mitigate the phenomenon of increased particle number in the electrode due to particle cracking, thereby improving the battery's lifespan characteristics.
[0157] In one exemplary embodiment of this application, the average particle size (D50) of the single particle is 1 μm to 18 μm smaller than the average particle size (D50) of the secondary particle.
[0158] For example, the average particle size (D50) of the single particle can be 1 μm to 16 μm smaller, 1.5 μm to 15 μm smaller, or 2 μm to 14 μm smaller than the average particle size (D50) of the secondary particles.
[0159] When the average particle size (D50) of the single particle is smaller than the average particle size (D50) of the secondary particle, for example, when the above range is met, the single particle can have excellent particle strength even if it is formed into a small particle size. Therefore, the excellent particle strength can reduce the phenomenon of increased particle number in the electrode due to particle cracking, thereby improving the battery life characteristics and energy density.
[0160] According to other exemplary embodiments of this application, based on 100 parts by weight of positive electrode active material, the content of the single particles is 15 parts by weight to 100 parts by weight. Based on 100 parts by weight of positive electrode active material, the content of the single particles can be 20 parts by weight to 100 parts by weight, or 30 parts by weight to 100 parts by weight.
[0161] For example, based on 100 parts by weight of positive electrode active material, the content of the single particles can be 15 parts by weight or more, 20 parts by weight or more, 25 parts by weight or more, 30 parts by weight or more, 35 parts by weight or more, 40 parts by weight or more, or 45 parts by weight or more. Based on 100 parts by weight of positive electrode active material, the content of the single particles can be less than 100 parts by weight.
[0162] When the single particles are included within the aforementioned range, the combination with the aforementioned negative electrode material can exhibit excellent battery characteristics. In particular, when the amount of the single particles is 15 parts by weight or more, the phenomenon of increased particle number in the electrode due to particle cracking during the calendering process after electrode manufacturing can be mitigated, thereby improving the battery's lifespan characteristics.
[0163] In one exemplary embodiment of this application, the lithium composite transition metal compound may further comprise secondary particles, and the amount of the secondary particles may be 85 parts by weight or less based on 100 parts by weight of the positive electrode active material. Based on 100 parts by weight of the positive electrode active material, the amount of the secondary particles may be 80 parts by weight or less, 75 parts by weight or less, or 70 parts by weight or less. Based on 100 parts by weight of the positive electrode active material, the amount of the secondary particles may be 0 parts by weight or more.
[0164] When the above range is met, the aforementioned effect due to the presence of single-particle positive electrode active material can be maximized. When the positive electrode active material contains secondary particles, its composition may be the same as or different from the exemplary composition of the single-particle positive electrode active material, and may refer to the form of single-particle aggregates.
[0165] In one exemplary embodiment of this application, in 100 parts by weight of the positive electrode active material layer, the content of the positive electrode active material can be more than 80 parts by weight and less than 99.9 parts by weight, preferably more than 90 parts by weight and less than 99.9 parts by weight, more preferably more than 95 parts by weight and less than 99.9 parts by weight, and even more preferably more than 98 parts by weight and less than 99.9 parts by weight.
[0166] The positive electrode active material layer may include a positive electrode conductive material and a positive electrode binder in addition to the above-mentioned positive electrode active material.
[0167] In this case, the positive electrode conductive material is used to impart conductivity to the electrode and can be used without particular restriction, as long as the positive electrode conductive material has electronic conductivity without causing chemical changes in the battery. Specific examples include graphite, such as natural or artificial graphite; carbon-based materials, such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal cracking black, and carbon fiber; metal powders or metal fibers, such as copper, nickel, aluminum, and silver; conductive whiskers, such as zinc oxide and potassium titanate; conductive metal oxides, such as titanium oxide; or conductive polymers, such as polyphenylene derivatives, and any one or a mixture of two or more of them can be used.
[0168] Furthermore, the positive electrode adhesive is used to improve the bonding between positive electrode active material particles and the adhesion between the positive electrode active material and the positive electrode current collector. Specific examples may include polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene monomer (EPDM), sulfonated EPDM, styrene-butadiene rubber (SBR), fluororubber, or various copolymers thereof, and any one or a mixture of two or more of them may be used.
[0169] The separator separates the negative electrode from the positive electrode and provides a channel for the movement of lithium ions. It can be used without particular limitation, as long as it is typically used in secondary batteries. In particular, separators with excellent electrolyte moisture-holding capacity and low resistance to ion movement in the electrolyte are preferred. Specifically, porous polymer membranes can be used, such as porous polymer membranes formed from polyolefin polymers like ethylene homopolymers, propylene homopolymers, ethylene / butene copolymers, ethylene / hexene copolymers, and ethylene / methacrylate copolymers, or laminates of two or more layers thereof. Furthermore, typical porous nonwoven fabrics can be used, such as nonwoven fabrics made from high-melting-point glass fibers, polyethylene terephthalate fibers, etc. Additionally, coated separators containing ceramic components or polymer materials can be used to ensure heat resistance or mechanical strength, and can be selectively used as single-layer or multi-layer structures.
[0170] Examples of the electrolytes include, but are not limited to, organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel polymer electrolytes, solid inorganic electrolytes, and molten inorganic electrolytes that can be used to prepare lithium secondary batteries.
[0171] Specifically, the electrolyte may contain a non-aqueous organic solvent and a metal salt.
[0172] As the aforementioned non-aqueous organic solvent, aprotic organic solvents such as N-methyl-2-pyrrolidone, propylene carbonate, ethylene carbonate, butyl carbonate, dimethyl carbonate, diethyl carbonate, γ-butyrolactone, 1,2-dimethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, formamide, dimethylformamide, dioxolane, acetonitrile, nitromethane, methyl formate, methyl acetate, triphosphate, trimethoxymethane, dioxolane derivatives, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolium ketone, propylene carbonate derivatives, tetrahydrofuran derivatives, ethers, methyl propionate, and ethyl propionate can be used.
[0173] In particular, among carbonate-based organic solvents, ethylene carbonate and propylene carbonate, as cyclic carbonates, have high dielectric constants as high-viscosity organic solvents, thus enabling good dissociation of lithium salts. Therefore, they are preferred to be used. When such cyclic carbonates are mixed with low-viscosity and low-dielectric-constant linear carbonates such as dimethyl carbonate and diethyl carbonate in a suitable ratio, electrolytes with high conductivity can be prepared. Therefore, such combinations are more preferred to be used.
[0174] Lithium salts can be used as the metal salts, and these lithium salts are materials that are readily soluble in non-aqueous electrolytes. For example, anions selected from F- and Cl- can be used as the anions of the lithium salts. - I - NO3 - N(CN)2 - BF4 - ClO4 - PF6 - (CF3)2PF4 - (CF3)3PF3 - (CF3)4PF2 - (CF3)5PF - (CF3)6P - CF3SO3 - CF3CF2SO3 - (CF3SO2)2N - (FSO2)2N - CF3CF2(CF3)2CO - (CF3SO2)2CH - (SF5)3C - (CF3SO2)3C - CF3(CF2)7SO3 - CF3CO2 - CH3CO2 - SCN - and (CF3CF2SO2)2N - One or more of the groups that make up the group.
[0175] In order to improve battery life characteristics, suppress battery capacity decline, and improve battery discharge capacity, the electrolyte may contain, in addition to the aforementioned electrolyte components, one or more additives, such as alkylene carbonate halide compounds like difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, n-glycol dimethyl ether, hexamethylphosphoryltriamine, nitrobenzene derivatives, sulfur, quinone imine dyes, and N-substituted compounds. Zolpidemone, N,N-substituted imidazolidinyl ether, ethylene glycol dialkyl ether, ammonium salt, pyrrole, 2-methoxyethanol or aluminum trichloride.
[0176] An exemplary embodiment of the present invention provides a battery module comprising the secondary battery as a unit cell, and a battery pack comprising the same. The battery module and the battery pack contain secondary batteries with high capacity, high rate capability, and high cycle performance, and therefore can be used as a power source for medium to large-sized devices selected from the group consisting of electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, and energy storage systems.
[0177] [Invention Model]
[0178] Preferred embodiments will be presented below to aid in understanding the invention, but these embodiments are provided merely to illustrate the invention, and it will be apparent to those skilled in the art that various changes and modifications are possible within the scope and spirit of the invention, and such changes and modifications naturally fall within the scope of the appended claims.
[0179] <Example 1>
[0180] Manufacturing of negative electrode
[0181] 0.5 wt% polyvinylidene fluoride (PVDF) was added to dimethylformamide (DMF), and the resulting mixture was sonicated for 1 hour, followed by stirring overnight. Subsequently, 2 wt% Si was added to the solution, and the resulting solution was stirred for 3 hours, followed by stirring for another hour while ethanol was added dropwise. After centrifugation three times with ethanol, the solution was vacuum dried at 70°C for 12 hours, and then heat-treated in a high-temperature furnace at 700°C in an Ar atmosphere for 1 hour to obtain carbon-coated Si. In this case, the amount of carbon in the coating was 7% relative to Si, the coating thickness was 10 nm, and the amount of F was 0.2 wt% relative to Si.
[0182] The negative electrode slurry was prepared as follows: the Si prepared above was used as the active material (containing an F-containing carbon coating in 100% Si), and the active material, the plate-shaped graphite conductive material (average particle size 3.5 μm) as the first conductive material, the SWCNT as the second conductive material, and the acrylamide as the binder were added to distilled water as the solvent in a weight ratio of 79.5:10:0.5:10.
[0183] Subsequently, a negative electrode active material layer was coated onto a Cu foil with a thickness of 15 μm to a thickness of 30 μm, then dried at 130 °C for 12 hours, and rolled with a negative electrode porosity of 40% to manufacture the negative electrode.
[0184] <Example 2>
[0185] The negative electrode was manufactured in the same manner as in Example 1, except that 2% by weight of polyvinylidene fluoride (PvdF) was added to dimethylformamide (DMF), and in this case, the amount of carbon in the coating was 12% relative to Si, the coating thickness was 13 nm, and the amount of F was 0.4% by weight relative to Si.
[0186] <Example 3>
[0187] The negative electrode was manufactured in the same manner as in Example 1, except that 0.25% by weight of polyvinylidene fluoride (PvdF) was added to dimethylformamide (DMF), and in this case, the amount of carbon in the coating was 4% relative to Si, the coating thickness was 5 nm, and the amount of F was 0.003% by weight relative to Si.
[0188] <Example 4>
[0189] The negative electrode was manufactured in the same manner as in Example 1, except that the negative electrode slurry was prepared by using the Si prepared above as the active material (containing an F-containing carbon coating in 100% Si), and adding the active material, SWCNT as the conductive material, and acrylamide as the binder in a weight ratio of 89.5:0.5:10 to distilled water as the solvent.
[0190] <Example 5>
[0191] The negative electrode was manufactured in the same manner as in Example 1, except that the negative electrode slurry was prepared as follows: the Si prepared above was used as the active material (containing an F-containing carbon coating in 100% Si), and the active material, dotted carbon black (Super-P) as the conductive material, plate-shaped graphite conductive material (average particle size of 3.5 μm), and SWCNT, and acrylamide as the binder were added to distilled water as the solvent in a weight ratio of 79.5:5:5:0.5:10.
[0192] <Comparative Example 1>
[0193] The negative electrode was manufactured in the same manner as in Example 1, except that Si active material (100% Si) was used, which did not contain a carbon coating doped with F.
[0194] <Comparative Example 2>
[0195] The negative electrode was manufactured in the same manner as in Example 1, except that SiO active material was used.
[0196] <Comparative Example 3>
[0197] The negative electrode was manufactured in the same manner as in Example 1, except that SiO containing 5% by weight of carbon coating was used instead of F (carbon coating included in 100% SiO).
[0198] <Comparative Example 4>
[0199] The negative electrode was manufactured in the same manner as in Example 1, except that a Si active material (100% Si) containing an undoped F carbon coating was used.
[0200] Manufacturing of Secondary Batteries
[0201] The positive electrode slurry was prepared in the following manner: LiNi, which serves as the positive electrode active material, was used... 0.6 Co 0.2 Mn 0.2 O2 (average particle size (D50): 15 μm), carbon black (product name: Super C65, manufacturer: Timcal) as a conductive material, and polyvinylidene fluoride (PVdF) as a binder are added to N-methyl-2-pyrrolidone (NMP) (solid concentration: 78 wt%) as a solvent for forming the positive electrode slurry in a weight ratio of 97:1.5:1.5.
[0202] Both surfaces of the aluminum current collector (thickness: 12μm), used as the positive electrode current collector, were coated with positive electrode slurry, with a loading of 537mg / 25cm. 2 The aluminum current collector is rolled and dried in a vacuum oven at 130°C for 10 hours to form a positive electrode active material layer (thickness: 65 μm), thereby preparing a positive electrode (positive electrode thickness: 77 μm, porosity: 26%).
[0203] A polyethylene separator is inserted between the positive electrode described above and the negative electrode of each embodiment and comparative example, and an electrolyte is injected therein to manufacture a lithium secondary battery.
[0204] The electrolyte is obtained by adding 3% by weight of vinylene carbonate (based on the total weight of the electrolyte) to an organic solvent (in which fluoroethylene carbonate (FEC) and diethyl carbonate (DMC) are mixed in a volume ratio of 30:70), and adding LiPF6 as a lithium salt at a concentration of 1M.
[0205] Experimental Example 1: Evaluation of the initial efficiency of lithium secondary batteries
[0206] The initial charge-discharge capacity and initial efficiency of the lithium secondary batteries manufactured in the examples and comparative examples were evaluated using an electrochemical charge-discharge apparatus.
[0207] Under the conditions of charging (0.1C CC / CV charging, 0.005V, 0.005C cut-off) and discharging (0.1C CC discharging, 1.5V cut-off), the capacity and efficiency per gram of the lithium secondary battery were calculated, and the results are shown in Table 1 below.
[0208] [Table 1]
[0209] Example 1 3003 2762 92 Example 2 2990 2751 92 Example 3 3030 2727 90 Example 4 3005 2674 89 Example 5 2997 2727 91 Comparative Example 1 3059 2753 90 Comparative Example 2 1640 1230 75 Comparative Example 3 1642 1199 73 Comparative Example 4 2987 2629 88
[0210] Experimental Example 2: Evaluation of Capacity Retention Rate of Lithium Secondary Batteries
[0211] The capacity retention rates of the lithium secondary batteries fabricated in the Examples and Comparative Examples were evaluated using an electrochemical charger-discharger.
[0212] Under the conditions of charging (0.5C CC / CV charging, 0.005V, 0.005C cut-off) and discharging (0.5C CC discharging, 1.0V cut-off) the lithium secondary battery, the number of cycles until the capacity reached the 80% level was confirmed.
[0213] The capacity retention rate at the Nth cycle was evaluated by the following formula. The results are shown in Table 2 below.
[0214] [Formula]
[0215] Capacity retention rate (%) = {(Discharge capacity at the Nth cycle) / (Discharge capacity at the 1st cycle)} × 100
[0216] [Table 2]
[0217]
[0218] Comparative Example 1 in Table 1 and Table 2 is a case where pure Si is used as the active material but no F-doped carbon coating is included; and Comparative Example 4 is a case where pure Si is used as the active material but only a single carbon coating is included. That is, it can be confirmed that Comparative Examples 1 and 2 use the same type of active material, the initial efficiency is in a range similar to that of the Examples, but the capacity retention rate and discharge capacity in Table 2 decrease. This is a result of being unable to alleviate the volume expansion of the active material and being unable to form a stable LiF film.
[0219] In addition, it can be confirmed that in the case of the present invention, pure Si (the silicon-based active material contains one or more selected from the group consisting of SiOₓ (x=0) and SiOₓ (0<x<2), and based on 100 parts by weight of the silicon-based active material, the content of the SiOₓ (x=0) is 70 parts by weight or more) is used as the active material, and compared with the cases of Examples 1 to 4, the initial efficiency is deteriorated in the cases of Comparative Example 2 (SiO active material) and Comparative Example 3 (SiO active material).
[0220] Specifically, Comparative Example 2 is the case where an F-doped carbon layer is used on SiO, while Comparative Example 3 is the case where only a carbon coating is used on SiO. It can be confirmed that in both cases, the initial efficiency can be improved by 1% to 2% compared with SiO active material without other treatment, but the initial efficiency is reduced compared with the example, and the charge / discharge capacity is reduced to a very low level compared with the case where pure Si is used as active material.
[0221] In other words, Comparative Examples 2 and 3, which use SiO active material (a 1:1 composite of Si and SiO2), exhibit low initial efficiency due to an irreversible reaction between the oxide and Li caused by the Si active material. However, due to the subsequent reversible reaction, the capacity retention is good compared to that of the Si active material (see Table 2). However, as can be confirmed in Table 1, a drawback of Comparative Examples 2 and 3 is that their theoretical capacity is much lower than that of Si, and it is impossible to achieve charge / discharge capacities comparable to those of Example 1 of this invention when using the SiO active material. Therefore, it can be confirmed that the high-capacity lithium secondary battery anticipated in this application cannot be manufactured.
[0222] In summary, as can be confirmed in Tables 1 and 2, the negative electrode composition according to an exemplary embodiment of the present invention is such a negative electrode composition in which, when using a silicon-based active material (which is a high-capacity material) to manufacture a high-capacity lithium secondary battery, the properties of the silicon-based active material itself are adjusted, rather than the properties of the conductive material and the binder are adjusted according to the volume expansion of the silicon-based active material, and the surface of the silicon-based active material is characterized by comprising a carbon coating, and by using a carbon coating doped with fluorine (F) as the carbon coating, the rapid volume expansion of the silicon-based active material during charge and discharge is mitigated, while the fluorine doped into the carbon coating can react with FEC, thereby forming a more stable LiF film on the negative electrode in addition to the formation of an SEI layer.
[0223] Furthermore, Examples 1 and 2 are cases in which the amount of F doped is greater than that in Example 3. Since the fluorine content is as described above, the coating thickness is appropriate, and thus it can be confirmed that the capacity per unit weight is much better than that in Example 3.
Claims
1. A negative electrode composition, the negative electrode composition comprising: a silicon-based active material; a negative electrode conductive material; and a negative electrode binder, wherein a surface of the silicon-based active material comprises a carbon coating, the carbon coating is doped with fluorine, and the silicon-based active material comprises one or more selected from the group consisting of Si and SiOₓ, wherein 0<x<2, and based on 100 parts by weight of the silicon-based active material, the content of Si is 70 parts by weight or more, wherein the negative electrode conductive material comprises: a planar conductive material; and a linear conductive material, and based on 100 parts by weight of the negative electrode conductive material, in the negative electrode conductive material, the content of the planar conductive material is 80 parts by weight or more and 99.5 parts by weight or less; and the content of the linear conductive material is 0.5 parts by weight or more and 20 parts by weight or less.
2. The negative electrode composition according to claim 1, wherein based on 100 parts by weight of the negative electrode composition, the content of the silicon-based active material is 60 parts by weight or more.
3. The negative electrode composition according to claim 1, wherein based on 100 parts by weight of the negative electrode composition, the content of the negative electrode conductive material is 10 parts by weight or more and 40 parts by weight or less.
4. The negative electrode composition according to claim 1, wherein the fluorine doped in the carbon coating is formed by a single bond between carbon and fluorine.
5. The negative electrode composition according to claim 1, wherein based on 100 parts by weight of the silicon-based active material, the content of the fluorine is 0.1 parts by weight or more and 20 parts by weight or less.
6. A method of preparing a negative electrode composition, the method comprising: providing a silicon-based active material, the silicon-based active material comprising a fluorine-doped carbon coating on a surface thereof; forming a mixture by mixing a negative electrode conductive material and a negative electrode binder; performing first mixing by adding water to the mixture; and adding the silicon-based active material comprising the fluorine-doped carbon coating to the mixed mixture obtained thereby to perform second mixing, wherein the silicon-based active material comprises one or more selected from the group consisting of Si and SiOₓ, wherein 0<x<2, and based on 100 parts by weight of the silicon-based active material, the content of Si is 70 parts by weight or more, wherein the negative electrode conductive material comprises: a planar conductive material; and a linear conductive material, and based on 100 parts by weight of the negative electrode conductive material, in the negative electrode conductive material, the content of the planar conductive material is 80 parts by weight or more and 99.5 parts by weight or less; and the content of the linear conductive material is 0.5 parts by weight or more and 20 parts by weight or less.
7. The method according to claim 6, wherein the providing of the silicon-based active material comprising the fluorine-doped carbon coating on the surface thereof comprises: adding the silicon-based active material to a fluorine-containing polymer solution; bonding the fluorine-containing polymer to the surface of the silicon-based active material by adding ethanol to the polymer solution; and carburizing the bonded polymer.
8. The method of claim 6, wherein during the first mixing and the second mixing, the mixing is performed at 2,000 rpm to 3,000 rpm for 10 minutes to 60 minutes.
9. A negative electrode for a lithium secondary battery, the negative electrode for a lithium secondary battery comprising: Negative current collector layer; and A negative electrode active material layer is formed on one or both surfaces of the negative electrode current collector layer, the negative electrode active material layer comprising the negative electrode composition according to any one of claims 1 to 5.
10. The negative electrode as claimed in claim 9, wherein the negative electrode current collector layer has a thickness of 1 μm or more and 100 μm or less, and The negative electrode active material layer has a thickness of more than 20 μm and less than 500 μm.
11. A lithium secondary battery, the lithium secondary battery comprising: positive electrode; The negative electrode for a lithium secondary battery according to claim 9; A membrane disposed between the positive electrode and the negative electrode; and Electrolytes.
Citation Information
Patent Citations
Anode for lithium ion battery
JP2009080971A
Non-Fire Alarm Rate Reduction P-type Receiver
KR1020210154386A
Preparation method of silicon-based negative electrode active material, silicon-based negative electrode active material, lithium ion battery negative electrode material and lithium ion battery
CN108598413A
KR20200089568A